Original article Astroglia disturbances during development of the central nervous system in fetuses with Down’s syndrome - Zdaniuk, Grzegorz; Wierzba-Bobrowicz, Teresa; Szpak, Grażyna M.; Stępień, Tomasz (Folia Neuropathologica, 2011)
Down’s syndrome (DS), caused by aneuploidy of chromosome 21, is the most common chromosomal disorder. The most significant symptom of this disorder is mental retardation. Neuropathological changes found in the DS central nervous system (CNS), such as reduced number of neurons, alteration of synapses and synaptic spines or delayed myelination have been widely described. But there are only a few studies of DS-related glia disturbances. A growing number of astroglia new functions have recently been described. In our study we compared the number of astrocytes and radial glial cells in the frontal lobe of DS fetuses at 18-20 weeks of gestation with that observed in age-matched controls. We found a substantially increased number of glial fibrillary acid protein (GFAP) positive cells in all age range samples of DS brains. We also noticed that in our study astrocytes in DS brains seem to be morphologically more mature than in controls of corresponding age. The same observation was made for radial glia. Taking into consideration the role played by astroglia during CNS development we believe that any change in their number, reduced or increased, can affect CNS development and lead to disturbances of both neurogenesis and synaptogenesis. A possible correlation between the increased number of astroglia and disturbances in CNS development is discussed.